Evaluation of six clinical prognostic scores in NSCLC patients undergoing first line chemoimmunotherapy - Sun, Jiaqi; Li, Dan; Liu, Jiayin; Wang, Lan; Wang, Long; Han, Jing; Zhang, Xue; Zhou, Xinliang; Feng, Li; Fan, Zhisong; Zuo, Jing; Wang, Yudong (Frontiers in Immunology, 2026)
BackgroundThe study aimed to evaluate the effectiveness of six prognostic scores for predicting the outcomes to first-line chemoimmunotherapy (CIT) in non-small cell lung cancer (NSCLC) patients.Materials and methodsNSCLC patients receiving first-line CIT were included. The prognostic scores evaluated were RMH, MDACC, MDACC+NLR, MDA-ICI, LIPI, and GRIm. Survival curves were generated using the Kaplan–Meier method, and univariate and multivariate analyses were conducted via the Cox proportional hazards regression model. The C−index and time−dependent AUC were calculated to comprehensively quantify and compare the predictive performance of each system. The Log−rank test and False Discovery Rate (FDR) correction was employed to compare survival outcomes across different risk groups defined by the six prognostic scoring systems.ResultsA cohort of 298 NSCLC patients was analyzed. The median overall survival (mOS) of patients receiving first-line CIT was 36.5 months (95%CI: NE-NE), and the median progression-free survival (mPFS) was 14.5 months (95%CI: 11.9-17.1). Multivariate analysis showed that bone metastasis (P = 0.042), and more than two metastatic sites (P = 0.031) as independent predictors of poor OS. In quantitative performance comparison, RMH achieved the highest C-indices for both OS (0.672, 95%CI: 0.531-0.813) and PFS (0.652, 0.564-0.737); MDACC also performed well, with C-indices for OS (0.651, 0.564-0.737) and PFS (0.615, 0.554-0.738). Time-dependent AUC analysis showed that MDA-ICI attained the highest 1-year OS and PFS AUC (0.630 and 0.592), followed by the MDACC+NLR (0.600 and 0.571). Based on log-rank testing and following FDR correction, only the MDACC maintained a statistically significant association with OS (high-risk 14.0 vs. intermediate-risk 34.6 vs. low-risk NR months; P = 0.003, Q = 0.036). For PFS, the MDACC+NLR score showed a marginal significance after FDR correction (Q = 0.054).ConclusionsThe RMH, MDACC, and MDACC+NLR scoring systems all demonstrate prognostic utility in the NSCLC patients treated with first-line CIT, and the optimal choice among them may depend on the specific clinical context and the outcome metric of primary interest.